Anatomic Targets for Breast Reconstruction Neurotization: Past Results and Future Possibilities. Issue 2 (February 2019) - Gatherwright, James; Knackstedt, Rebecca; Djohan, Risal
Abstract : Abstract: The concept of providing neurotized autologous breast reconstruction is not novel, but the introduction of cadaveric nerve grafts has allowed for the development of new techniques and a resurgence in academic interest. There has been a surge in the number of publications regarding neurotized autologous breast reconstruction. However, recent articles and reviews have focused mainly on autologous, abdominal-based reconstruction. The sensory innervation of the most commonly used autologous tissues has been well described, allowing surgeons to perform accurate and reproducible dissections. However, there are numerous options for autologous breast reconstruction, and not all patients are candidates for abdominally based reconstruction. As more patients inquire to their possible reconstruction options, plastic surgeons will have to be well versed in the different neurotized options and appreciate the technical aspects associated with reconstructive success. In this review, we aim to discuss both established anatomic targets for autologous flap neurotization and future directions.